FEATURES OF IMMUNOCOMPETENT CELLS IN THE PATIENTS WITH CHRONIC LYMPHOCYTIC LEUKEMIA AT PRIMARY DIAGNOSIS - N. V. Isaeva; G. A. Zaitseva; I. A. Dokshina (Медицинская иммунология)
Some basic parameters of immune profile have been investigated in 140 patients with chronic lymphocytic leukemia (CLL). There was shown that the cohort of CLL patients is heterogeneous for their immune profile as early as at primary diagnosis stage, showing sufficient differences in the numbers of immunocompetent cells in peripheral blood. In most cases, the interpretation of appropriate quantitative characteristics is quite difficult, if based on the conventional criteria. The numbers of activated T-lymphocytes and NK-cells were proven to be the most informative parameters of cellular immunity in this cohort. Progression of leukemic events shows a close association with only a single parameter under study, i.e., CD4+/CD8+ cell ratio.